Ministry of Trade and Industry Decree No. 784 of the Year 2013 On Terminating the Realization of Protection Measures Against the Significant Increase in the Reinforcing Steel Imports Without Imposing Final Duties = وزارة التجارة والصناعة قرار رقم 784 لسنة 2013 بشأن إنهاء تحقيق الوقاية ضد الزيادة الكبيرة فى الواردات من صنف حديد التسليح دون فرض رسوم نهائية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.